“EQUALITY- REDUCING INEQUALITIES, ADVANCING HUMAN RIGHTS” - Dr. Inderpreet Kaur; Ms. Zakiya Ansari (International journal of economic perspectives, 2022)
Equality is a dynamic concept with many aspects and dimension and it cannot be ‘cribbed, cabined, confined’ within traditional and doctrinaire limits. To advance human rights, we must start at the roots of social issues and inequality and work to change unjust structures and systems. Our Indian Constitution has enshrined the equality to all its citizens irrespective of any discrimination under Article 14. It gives the equality before law and equal protection of laws to all. The title of this paper is theme of this year 2021- ie to reduce the inequalities throughout the world to promote the peace and harmony while celebrating the International Human Rights Day on 10th December of every year. To curb the violence against the vulnerable group such as Women as there are numbers of laws have been enacted but still she is not protected. Thus the main object is to propagate towards reducing and eliminating the inequalities in the world at large. This paper is an effort and appeal to all that WE all are humans irrespective of any discrimination like nation, colour, creed, sex etc. With humanitarian vision, we should work altogether for humanity. The following lyrics also appeals it beautifully: “Na Hindu banooga na Muslman banooga, Insaan Ki aulad hoon Insaan Bannu Ga“ There is no need to talk about the nationality, religion, caste and creed that I am Indian, I am an American, I am Hindu, I am Christian, I am woman and I am Child and so on.......... there is need to become a good HUMAN BEING.